Communication Barrier Analysis on Pandhalungan Students In An Osing Pesantren Environment - Nova Saha Fasadena (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article discusses the analysis of communication barriers of pandhalungan students in the Ossing pesantren environment. Cultural differences are faced by many students, especially when they first study at Pesantren, causing challenges, especially in terms of communication that must be done every day. Since this phenomenon often occurs in Osing boarding schools, where many students come from outside the region, it is crucial to research to reduce the impact of these cultural differences. This study focuses on identifying the communication barriers faced by out-of-area students in Osing boarding schools. The research method used was a qualitative approach conducted by conducting a field study. Information retrieval was done through purposive techniques in selecting informants and using observation, documentation, and semi-structured interviews in data collection. The collected data were then analyzed using the Miles and Huberman model, and data validity was ensured through the triangulation of techniques and sources. The results showed that the communication barriers faced by migrant santri in Osing boarding schools include language problems, differences in clothing, food variations, and understanding of time. However, migrant santri tend to adapt more quickly in Osing boarding schools because of the cultural similarities in the environment.